AI Integration in Islamic Fatwas: Opportunities and Challenges of Digital Ijtihad - Ilham Akbar Maulana; Firdaus Sutan Mamad; Urwatul Wusqa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This article aims to analyze the emergence of technology-based fatwas and the responses of Islamic scholars to the use of Artificial Intelligence (AI) in Islamic legal decision-making. The study focuses on the opportunities for integrating digital technology into the process of ijtihad while examining the associated epistemological challenges, the authority of Islamic scholars, and algorithmic bias. A qualitative approach based on a literature review was employed by examining classical sources of uṣūl al-fiqh alongside contemporary literature on the application of AI in Islamic legal discourse. The analysis was conducted using the framework of maqāṣid al-sharīʿah to assess the extent to which AI-assisted fatwas align with the objectives of Islamic law. The findings indicate that AI can accelerate the retrieval of legal evidence, broaden analytical capabilities, and enhance the relevance of fatwas in addressing contemporary issues such as biotechnology vaccines, Islamic financial technology (fintech), and e-commerce transactions. However, AI cannot replace Islamic scholars as mujtahids; rather, it functions as a decision-support tool in the process of legal reasoning. The major challenges identified include algorithmic bias, concerns over the legitimacy of scholarly authority, and social resistance to digitally generated fatwas. This study underscores the need for a new paradigm of digital ijtihad that positions AI as a complementary tool operating under the supervision of qualified Islamic scholars and guided by the ethical principles of Islamic law. Such an approach would enable technology-assisted fatwas to serve as valid, contextual, and beneficial innovations in contemporary Islamic jurisprudence.